Sex hormones and choice under risk - Burkhard C. Schipper (University of California, Department of Economics, 2012)
We correlate choice under risk in Holt-Laury lottery tasks for gains and losses with salivary testosterone, estradiol, progesterone, and cortisol, the use of hormonal contraceptives, menstrual cycle information as well as the digit ratio (2D:4D) in more than 200 subjects. Risk aversion is negatively correlated with testosterone and positively correlated with cortisol, a stress hormone, for gains only. In males, testosterone is negatively correlated with risk aversion for gains only. In females, cortisol is marginally significantly positively correlated with risk aversion for gains only. No other significant correlations between risk aversion and salivary hormones are observed. In females, testosterone and progesterone are positively correlated with reflection, i.e., risk aversion for gains and risk seeking for losses. Testosterone is negatively correlated with consistency of preferences in females, while estradiol is negatively correlated with consistency of preferences in males. No significant correlations between risk aversion and the menstrual cycle or the digit ratio are observed. Females on hormonal contraceptives are more likely to make consistent choices although this may be due to a selection effect. Risk aversion is positively correlated with being female for losses only. Yet, if we control for salivary hormones we are surprised to find a negative correlation between female and risk aversion for gains.
Keywords: C91; C92; D44; D81; D87; 330; Hormones; Menstrual cycle; Contraception; Digit ratio; 2D:4D; Gender; Risk behavior; Endocrinological economics; Holt-Laury; Risk aversion; Risk seeking; Reflection effect; Prospect theory